Potential of Marine Algae as Peripheral Neuropathy Therapy: An Article Review - Widad, Najwa; Paerdoe, Lalu Dane Pemban; Qindi, Ahmad Sa’bi Al; Yulianti, Arwinda Febri; Hunaifi, Ilsa (Jurnal Biologi Tropis, 2025)
Peripheral neuropathy is a peripheral nerve disorders involving sensory, motor, or mixed nerves. First-line therapies for peripheral neuropathy, such as analgesics and SSRIs, often yield suboptimal therapeutic responses, have side effects, and provide inadequate disease control. Therefore, there is a need for adjuvant therapy utilizing bioactive compounds from natural sources, one of which is marine algae. Marine algae contain various compounds that have the potential to serve as safe and effective alternative adjuvant therapies for peripheral neuropathy. The literature used was collected from the PubMed, ScienceDirect, and Google Scholar databases with restrictions: publication years from 2015 to 2025 and in either Indonesian or English. The review indicated that several compounds found in marine algae, such as florotanins, terpenoids, polysaccharides, peptide proteins, essential amino acids, and omega-3 fatty acids, exhibited biological activities such as antioxidant, anti-inflammatory, and neuroprotective effects. These compounds showed potential as alternative adjuvant therapies for peripheral neuropathy. In conclusion, the compounds in marine algae demonstrated various biological activities, suggesting their potential for development as alternative adjuvant therapies for peripheral neuropathy. Further research is needed to test their safety and effectiveness before being applied in clinical practice.